Isometric Expansions of Quantum Algebra of Linear Bounded Operators - Zolotarev, V. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
The isometric expansion {V_s,+V_s}_s=1^2 for a quantum algebra of linear bounded nonunitary operators {T_1,T_2}, which is given by commutative relation T_1T_2=qT_2T_1 (|q|=1), is constructed. Basic properties of characteristic function S(z) corresponding to isometric expansion {V_s,+V_s}_s=1^2 for given quantum algebra {T_1,T_2} are described. Mathematics Subject Classification 2000: 47A45.